2013
DOI: 10.1002/grl.50170
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite deformation mechanism maps for better prediction of strain partitioning

Abstract: [1] A meta-analysis of existing experimental deformation data for magnetite and other spinel-structured ferrites reveals that previously published flow laws are inadequate to describe the general deformation behavior of magnetite. Using updated rate equations for oxygen diffusion in magnetite, we present new flow laws that closely predict creep rates similar to those found in deformation experiments and that can be used to predict strain partitioning between cubic Fe oxides and other phases in the Earth's crus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
4
32
0
Order By: Relevance
“…The Atkinson () flow laws predict very low dislocation creep temperatures at geologic strain rates and no deformation at laboratory strain rates. Our diffusion creep laws normalized to 10‐μm grain size (Figure b) are very close to those of both Till and Moskowitz () and Crouch and Robertson () at geological strain rates but indicate weaker magnetite behavior than either of the latter studies at laboratory strain rates. Atkinson () predicts unrealistically low deformation temperatures and stresses at both strain rates.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The Atkinson () flow laws predict very low dislocation creep temperatures at geologic strain rates and no deformation at laboratory strain rates. Our diffusion creep laws normalized to 10‐μm grain size (Figure b) are very close to those of both Till and Moskowitz () and Crouch and Robertson () at geological strain rates but indicate weaker magnetite behavior than either of the latter studies at laboratory strain rates. Atkinson () predicts unrealistically low deformation temperatures and stresses at both strain rates.…”
Section: Discussionsupporting
confidence: 83%
“…Their lower flow stresses probably result from their different experimental setup using a bending apparatus, which may promote brittle processes such as microcracking to a greater extent than our compression experiments. The dislocation creep law of Till and Moskowitz () is similar to that of Crouch and Robertson () at the lower strain rate and intermediate between our dry triaxial rates and Crouch and Robertson () at stresses above 50 MPa. The Atkinson () flow laws predict very low dislocation creep temperatures at geologic strain rates and no deformation at laboratory strain rates.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These microstructural relationships suggest that the brittle-ductile overprint occurred at lower temperatures, mainly ranging from amphibolite to greenschist facies conditions. Some of the shear zones contain Fe-Ti oxides, which are significantly weaker compared to silicate phases (e.g., Till and Moskowitz, 2013). We suggest that discrete parts of the shear zone were still deforming by ductile deformation mechanisms, whereas other zones Figure F15.…”
Section: Iodp Proceedingsmentioning
confidence: 81%
“…Experimental studies of magnetite, which is a non-silicate with a spinel structure like chromite, have revealed that magnetite can undergo intracrystalline deformation by dislocation creep (Hennig-Michaeli and Siemes, 1982;Müller and Siemes, 1972). Recent experiments on the deformation of magnetite (Till and Moskowitz, 2013) present new flow laws and give a stress exponent value around 3, and hence we argue that the flow character is non-Newtonian, power-law creep with a stress exponent of around 3. Dislocation creep previously was not thought to be a dominant mechanism; instead, diffusional creep, which normally does not result in a strong crystallographic fabric (Wheeler, 2009) and intracrystalline deformation features, was considered the principal mechanism in the deformation of chromites (Ozawa, 1989).…”
Section: Microstructures In Highly Strained Chromitite: Underlying Phmentioning
confidence: 96%